Cadre Empowerment and Exclusive Breastfeeding Assistance for Pregnant Women in Sempor Village, Sempor District, Kebumen - Kusumastuti Kusumastuti; Dyah Puji Astuti; Eti Sulastri (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Breast milk is the ideal food for babies. Preparation for exclusive breastfeeding should start during pregnancy. The success of exclusive breastfeeding requires a lot of support from husband and family. Health volunteers are the spearhead of providing health information in the village so it is necessary to empower health volunteers in the socialization of exclusive breastfeeding to pregnant women. The purpose of the activity is to empower health volunteers regarding the importance of exclusive breastfeeding so that they can provide assistance on exclusive breastfeeding for pregnant women. The method of activity is to empower health volunteers about exclusive breastfeeding. Pre-test and post-test were carried out before the activity as an evaluation. The tools and materials used are LCD, screen, leaflet, questionnaire. A sample of 15 health volunteers. The results, before empowering health volunteers there were 8 health volunteers with sufficient knowledge of exclusive breastfeeding (53%) and 2 health volunteers with good knowledge of exclusive breastfeeding (13.3%). After empowering health volunteers, there was an increase in the knowledge of health volunteers, namely 13 health volunteers had good knowledge of exclusive breastfeeding (86.6%) and the remaining 2 health volunteers had sufficient knowledge (13.3%). At the mentoring stage, 15 health volunteers managed to provide assistance to 15 pregnant women who were willing to prepare themselves during pregnancy to provide exclusive breastfeeding to their babies after birth. The conclusion is that there is an increase in knowledge of health volunteers after empowering health volunteers so that pregnant women get assistance in preparing exclusive breastfeeding.